Evaluation of the Legal Framework for Digital Business in Indonesia in Addressing Technological Developments and Regulatory Challenges - Taufan, Ridwan Anthony; Sara, Rineke (Ridwan Institute, 2025)
The development of digital technology has driven the growth of digital-based businesses in Indonesia, creating new challenges in legal aspects. Digital businesses cover various sectors, such as e-commerce, financial technology (fintech), and other digital platform-based services. Along with these developments, various legal issues have emerged, including consumer protection, personal data protection, electronic transactions, and dispute resolution in digital businesses. Therefore, a comprehensive legal review is needed to understand the applicable regulations and mechanisms for handling digital business legal cases in Indonesia. This study aims to analyze the legal framework governing digital businesses in Indonesia, examine the dispute resolution mechanisms in digital businesses, and identify challenges in implementing existing regulations. This study uses a normative legal research method, which focuses on the analysis of laws and regulations, legal doctrines, and relevant literature. The approaches used include a statute approach to examine regulations related to digital businesses, as well as a conceptual approach to understand the legal theory that supports legal protection and certainty in this sector. The analysis results are expected to contribute to more effective digital business development regulations and encourage the creation of a legal system that is adaptive to technological developments. Additionally, this study aims to provide recommendations for the government, regulators, and business actors in increasing legal certainty and protection for parties involved in digital business in Indonesia. Thus, it is expected that digital business legal regulations can further support a safe, transparent, and sustainable business ecosystem in the digital era.